Characterization of myofibrils cold structural deformation degrees of frozen pork using hyperspectral imaging coupled with spectral angle mapping algorithm - Cheng, Weiwei; Sun, Da-Wen; Pu, Hongbin; Wei, Qingyi (Food chemistry, 2018)
•HSI was used by the first time to assess cold structural deformation of myofibril.•SAM was used for feature extraction in HSI for the first time.•PLSR models built for predicting deformation degrees showed good results.•SAM was promising to be used as another feature extraction algorithm for HSI.•The implications of frozen pork spectrum in the NIR region were analyzed. The study investigated the possibility of using hyperspectral imaging (HSI) in the spectral range of 1000–2200nm to characterize myofibrils cold structural deformation degrees of frozen pork samples. The HSI images of pork samples frozen under different freezing rates were acquired in the frozen state without thawing. The myofibrils cold structural deformation degrees were evaluated by surface hydrophobicity (S0ANS) and Ca2+-ATPase activity. Spectral angle mapping (SAM) algorithm was used for the first time to extract the spectral information for regression. Compared with the optimized partial least square regression (PLSR) models based on selected wavebands by successive projections algorithm (SPA), the optimized PLSR models developed based on the spectral angles calculated by the SAM algorithm achieved comparable or even better performance with R2P of 0.896 for S0ANS and 0.879 for Ca2+-ATPase activity, respectively. The implications of the frozen meat spectrum were also analyzed in the current study.